Microbial Safety of Beef Along Beef Value Chains in the Ashaiman Municipality of Ghana - Adjei, Vida Yirenkyiwaa; Mensah, Gloria Ivy; Parry-Hanson Kunadu, Angela; Tano-Debrah, Kwaku; Ayi, Irene; Addo, Kennedy Kwasi (Frontiers in Veterinary Science, 2022)
Food from animal sources continues to be a significant food safety hazard. The study determined the microbial quality and safety of beef along beef value chains with case studies in the Ashaiman municipality of Ghana. Raw beef samples were collected from four slaughter slabs in the Ashaiman Municipality and analyzed using standard microbiological methods to determine the quality and prevalence of specific pathogens including Salmonella species, Listeria monocytogenes and Brucella species as well as Toxoplasma gondii, Cyclospora cayetanensis and Cryptosporidium parvum. Data regarding food safety knowledge and practices were collected and observed from stakeholders (cattle farmers, butchers and beef retailers). Salmonella Typhimurium was isolated from 7.5% (6/80) of the total raw beef sampled. However, L. monocytogenes, Brucella spp., T. gondii, C. cayetanensis and C. parvum were not isolated in the study. The mean level of microbial contamination of beef from the slaughter slabs/abattoir (5.2 Log10 CFU/g) was not significantly different (p>0.05) from the mean level observed at retail points (5.4 Log10 CFU/g). However, the mean coliform count of 4.3 Log10 CFU/g recorded at retail shops exceeded the permissible limits of 104 CFU/g (4 Log10 CFU/g) required by the Ghana Standards Authority for safety of meat and carcasses. Knowledge on food safety was at average level for butchers and retailers. Unhygienic practices and poor sanitary conditions at the abattoirs and retail shops observed could be the main contributing factors to microbial contamination of raw beef. Continuous education for meat handlers on issues of food safety and monitoring of slaughter activities will reduce the rate and level of contamination of beef.